Pertanggungjawaban Negara Terhadap Pencemaran Lintas Batas Negara (Studi Kasus: Kebakaran Hutan Di Indonesia Tahun 2019) - Bagas Ramadhan Putra; Wahyu Hariadi; Elly Kristiani Purwendah (Cakrawala Hukum: Majalah Ilmiah Fakultas Hukum Universitas Wijayakusuma, 2020)
A Haze of Smoke due to forest fire in Indonesia has been a long time crossed the border in Southeast Asia. This problem of haze still remain as an important agenda in ASEAN until now. Forest fires cause pollution and affect another country such as Malaysia and Singapore. ASEAN Agreement on Transboundary Haze Pollution (AATHP) is one among many ways to enhance cooperation at regional and sub-regional levels to overcome forest fires in the ASEAN region. Therefore, responsibility from the state is an important issue to discussed at the global level. The research method that being used is normative juridical. That is used are secondary data as the main data and primary data are used as supporting data, descriptive qualitative used to do analysis. The research was conducted to answer the problem of Indonesiaâ€™s responsibility for pollution.Keywords: ASEAN Agreement On Transboundary Haze Pollution, state responsibility, dispute resolutionÂ Abstrak. Kabut asap akibat kebakaran hutan di Indonesia telah lama melintasi perbatasan di Asia Tenggara. Masalah kabut asap masih tetap menjadi agenda penting di ASEAN hingga sekarang. Kebakaran hutan menyebabkan polusi dan berdampak pada wilayah negara lain seperti Malaysia dan Singapura. ASEAN Agreement on Transboubdary Haze Pollution (AATHP) adalah salah satu cara untuk meningkatkan kerja sama di tingkat regional dan sub-regional untuk mengatasi kebakaran hutan di kawasan ASEAN. Oleh karena itu, tanggung jawab negara adalah masalah penting untuk dibahas di tingkat global. Metode penelitian adalah yuridis normatif. Data yang digunakan adalah data sekunder sebagai data utama dan data primer sebagai data pendukung, deskriptif kualitatif digunakan untuk melakukan analisis. Penelitian ini dilakukan untuk menjawab masalah tanggung jawab Indonesia atas polusi.Kata Kunci: ASEAN Agreement On Transboundary Haze Pollution, tanggung jawab negara, penyelesaian sengketa